Adenocarcinoma of the Ampullary Glands of the Ductus Deferens in a Sprague-Dawley Rat. (June 2015) - Motohashi, Masaya; Wakui, Shin; Takahashi, Hiroyuki; Yoshida, Ayaka; Mutou, Tomoko; Ikegami, Masahiro; Asari, Masao; Inomata, Tomo
Spontaneously occurring proliferative lesions of the male accessory sex glands are infrequent in various strains of rats. In rodents, the ampullary glands are embedded in the prostate. Although 2 spontaneous cases of atypical hyperplastic lesions at the ampullary gland were previously described in Wistar rats, adenocarcinoma and/or adenoma in this gland have not been reported. This study describes adenocarcinomas in the bilateral ampullary glands in a 52-week-old intact male Sprague-Dawley rat housed as part of a control group in a toxicological experiment. At necropsy, the body weight (644.4 g) and the weight of the prostate with ampullary gland (2.75 g) were similar to others of the same control group, and it had a normal gross appearance. Histopathologically, both ampullary glands revealed microinvasive adenocarcinoma without vascular invasion. The morphological characteristics of the neoplasm varied in different regions of the gland. Other parts of the male accessory sex glands did not show proliferative lesions.